An Analysis of Applications Employed by Students to Cheat on Exams - Nurhaliza, Nisrina (EDUJ : English Education Journal, 2024)
This research intended to find out the reasons for students’ cheating, the applications used by students to cheat, and the solutions for educators to avoid students from cheating. This research used a mixed method. This research was conducted in STIKes Bina Cipta Husada Purwokerto. 16 students of Clinical and Community Pharmacy and two English lecturers were the subjects of this research. Questionnaires and interviews were conducted to collect the data. Then, the data was analyzed using data reduction, data display, and conclusion drawing. The result obtained that there are four reasons for students’ cheating such as unconfident to do exams, lack of motivation, dislike of English, and social situational factors. Meanwhile, the applications employed by students to cheat on exams such as Gemini, DeepL, Bing, Roboguru, and Question. AI. To overcome students’ cheating problems, educators can do many things such as make anti-cheating pledges, different versions of tests, switch seating on every test day, use a questions pool, and application to detect plagiarism, and give compliments to students.